Analysis of minor actinide recycling using MOX fuel assemblies in a Boiling Water Reactor. (October 2018) - Alonso, Gustavo; Martinez, Eduardo; Ramírez, J. Ramón; Castillo, Rogelio; Castillo, Alejandro
Highlights: Plutonium and actinide recycling is assessed in a BWR. Four fuel rods are substituted by minor actinides rods and 8 water rods are included in a new MOX fuel assembly design. Reduction of plutonium and actinide is measured in an equilibrium reactor core cycle. Use of the MOX-MA fuel assemblies' prevents MA production. Abstract: BWR depleted fuel assemblies contain minor actinide (MA) and plutonium isotopes that must be stored for long periods of time for safety reasons, recycling of MA and plutonium is an alternative that could help to reduce the amount of high-level radioactive waste produced in a nuclear power reactor. Recycling of plutonium in MOX fuel is a proved option and several commercial reactors have MOX fuel as part of their reloads. MA recycling in a Boiling Water Reactor (BWR) has been analyzed previously by the authors showing that is feasible and the higher MA destruction is obtained when the minor actinide is embedded in uranium fuel assemblies instead of MOX fuel assemblies. However, the recycling of MA in UO2 fuel assemblies generates a higher amount of Pu-238 that is a precursor of Pu fissile isotopes increasing the amount of them in the depleted fuels employed for MA recycling. In this study a new BWR MOX fuel assembly design, that is called MOX-MA, is analyzed. The study takes an equilibrium cycle of a BWR as the reference cycle and then it proposes the use of an equivalent MOX fuel assembly in which 4 fuel rods are replaced by MA-bearing rods and 8 fuel rods are also replaced by water rods to increase moderation-to-fuel-ratio. The study aims to have the maximum amount of this new MOX BWR fuel assembly design, called MOX-MA, which can be used by reload in the core. The proposed MOX-MA fuel assembly can be used as a full reload and for a whole MOX-MA core there is no need to modify any of the control systems and this whole MOX-MA core produces the same amount of electricity than the UO2 reference equilibrium core. By using the MOX-MA fuel assemblies there is a plutonium net reduction of 33% and there is practically not production of MA.